2007
DOI: 10.5194/we-7-94-2007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a nurse shrub on seed deposition and seedling recruitment of the annual <i>Agriophyllum squarrosum</i>

Abstract: Abstract. The shrub Artemisia halodendron and the annual herb Agriophyllum squarrosum, which typically co-occur in a mobile sandy habitat in eastern inner Mongolia, China, were used to determine whether the presence of A. halodendron influences seed deposition and seedling recruitment of A. squarrosum under and around the shrub canopy in relation to wind direction, sampling position (windward vs. leeward sides) and distance from the shrub. The numbers of seeds deposited, seedlings emerged, and individuals recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…For instance, Rey Benayaset et al 2007studied different management techniques of the use of low-cost, low-impact techniques on restoration of Quercus coccifera oak forests, finding that competition had a strong impact on oak recruitment and that simple clipping of competing vegetation resulted in similar effects to those of more thorough and expensive treatments of competition removal. Other studies (Li et al, 2007) did try to detect facilitation between pairs of species but found prevailing competition between two species inhabiting mobile dunes, although the presence of one species created a wind barrier that modified prevailing airstreams and strongly influenced the spatial pattern of seed dispersal of the second species. This provided further evidence of the effect of shrubs as a source of spatial heterogeneity.…”
mentioning
confidence: 99%
“…For instance, Rey Benayaset et al 2007studied different management techniques of the use of low-cost, low-impact techniques on restoration of Quercus coccifera oak forests, finding that competition had a strong impact on oak recruitment and that simple clipping of competing vegetation resulted in similar effects to those of more thorough and expensive treatments of competition removal. Other studies (Li et al, 2007) did try to detect facilitation between pairs of species but found prevailing competition between two species inhabiting mobile dunes, although the presence of one species created a wind barrier that modified prevailing airstreams and strongly influenced the spatial pattern of seed dispersal of the second species. This provided further evidence of the effect of shrubs as a source of spatial heterogeneity.…”
mentioning
confidence: 99%